Jonathan Edwards on Justification Reform Development of the Doctrine in Eighteenth-Century New England. - Cho, Hyun-Jin. (Lanham : University Press of America, 2012)
.Cs7CED571B{text-align:left;text-indent:0pt;padding:0pt 0pt 0pt 0pt;margin:0pt 0pt 0pt 0pt}.cs5EFED22F{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:normal; }Jonathan Edwards (1703 & ndash;1758) was a preacher, theologian, and missionary to the Native Americans. This book asserts that Jonathan Edwards stood firmly on the Reformed tradition in the doctrine of justification.
Acknowledgments; Chapter One. Introduction; Chapter Two. Historical Development of the Doctrine of Justification before Jonathan Edwards; Chapter Three. The Historical Context of Jonathan Edwards on Justification; Chapter Four. Jonathan Edwards' Doctrine of Justification; Chapter Five. Jonathan Edwards' Continuity with the Reformation on Justification; Chapter Six. Conclusion: Jonathan Edwards' Contribution to Reformed Theology on Justification; Bibliography; Index.
Description based on print version record.
Keywords: Edwards, Jonathan, 1703-1758.; Justification (Christian theology) -- History of doctrines; Justification (Christian theology); Religion; Edwards, Jonathan, -- 1703-1758.; Justification (Christian theology) -- History of doctrines; Justification (Christian theology); RELIGION / Christian Theology / Soteriology; Electronic books